Role of Cardiac A2A Receptors Under Normal and Pathophysiological Conditions - Boknik, P.; Eskandar, J.; Hofmann, B.; Zimmermann, N.; Neumann, J.; Gergs, U. (Frontiers in Pharmacology, 2021)
This review presents an overview of cardiac A2A-adenosine receptors (AR). The localization of A2A-AR in the various cell types that encompass the heart and the role they play in force regulation in various mammalian species are depicted. The putative signal transduction systems of A2A-AR in cells in the living heart, as well as the known interactions of A2A-AR with membrane-bound receptors, will be addressed. The possible role that the receptors play in some relevant cardiac pathologies, such as persistent or transient ischemia, hypoxia, sepsis, hypertension, cardiac hypertrophy, and arrhythmias, will be reviewed. Moreover, the cardiac utility of A2A-AR as therapeutic targets for agonistic and antagonistic drugs will be discussed. Gaps in our knowledge about the cardiac function of A2A-AR and future research needs will be identified and formulated.